Effect of fibre volume fraction on energy absorption capabilities of E-glass/polyester automotive crash structures. (February 2016) - Esnaola, A.; Tena, I.; Aurrekoetxea, J.; Gallego, I.; Ulacia, I.
Abstract: Semi-hexagonal glass/polyester composite structures with different fibre volume fractions have been studied for automotive crash applications. Interlaminar shear strength and specific energy absorption capability of the material have been characterised in order to analyse the effect of the fibre content. Samples with different fibre content among 40% and 60% have shown similar interlaminar shear strength values, around 35–40 MPa. It has been found that by increasing the fibre percentage from 40% to 47% the specific energy absorption values of the material increased to 56 kJ/kg. For specimens with fibre volume fraction above 47%, the total amount of energy dissipated is similar. Increasing fibre content increases the linear density of the material and in fact, the same value of dissipated energy quantities with a higher linear density implies a decrease in the specific energy absorption values.